DNA Methylation Changes in Intron 1 of Triggering Receptor Expressed on Myeloid Cell 2 in Japanese Schizophrenia Subjects - Yoshino, Yuta; Ozaki, Yuki; Yamazaki, Kiyohiro; Sao, Tomoko; Mori, Yoko; Ochi, Shinichiro; Iga, Jun-ichi; Ueno, Shu-ichi (Frontiers in Neuroscience, 2017)
The microglia hypothesis of schizophrenia (SCZ) has recently been proposed. We previously reported that expression of triggering receptor expressed on myeloid cell 2 (TREM2) mRNA in leukocytes is elevated in SCZ compared to healthy controls. In this study, we examined the methylation rates of CpG sites at intron 1 of TREM2 and the relationship between methylation rates and mRNA expression. We selected four CpG sites at intron 1 of TREM2 that may theoretically bind major transcription factors. The methylation rates in 50 SCZ subjects were compared with those in 50 age-matched control subjects. The methylation rates were significantly lower in SCZ subjects at CpG 2 (17.0 ± 6.7 vs. 20.2 ± 5.0; p = 0.02) and CpG 3 (23.8 ± 8.2 vs. 28.1 ± 6.2; p = 0.01), and the average rate (15.3 ± 5.2 vs. 17.6 ± 3.9; p = 0.009) was also lower. We also observed a significant negative correlation between TREM2 mRNA expression and the methylation rates of CpG 2 (r = −0.252, p = 0.012). Lower methylation of intron 1 of TREM2 and higher TREM2 mRNA expression in SCZ subjects may be susceptibility markers for SCZ. This is a pilot study and the findings are needed to be validated in larger datasets and in myeloid cell types.